Integración y estudio del ácido carmínico en matrices de oligoestirenos y SiO2 - Fernández Quiroz, Jesús Daniel (Universidad Michoacana de San Nicolás de Hidalgo, 2009)
The free radical chain polymerization presents great versatility, since it can be applied to a great variety of monomers. This way, the production of organic polymers, along his history it has used chain transfer agents to regulate the growth during the free radical chain polymerization. In another sense, the production of inorganic polymers has been carried out actively in the last ten years, showing an exponential increase and being imposed as a technology of election by relation to other approaches, due principally to low operation temperature and high purity of compound obtained. On the other hand, the pigments use has being restricted increasingly could be the toxicity, as for his high price and lability. The present investigation considers the possibility of confining the pigments and thus, avoiding his prompt degradation; the carminic acid (CA) for their part, It is one of the natural pigments of more wide use and commercial importance. Hereby, using molecules of the CA an analysis is realized on his interaction into organic matrix based on oligostyrenes by different end group; as well as his integration into silicon dioxide matrix. In these systems there is identified an unusual aggregation-interaction of the molecules of the CA into organic and inorganic matrix. These conditions of interaction were observed by a morphologic, spectroscopic and thermal analysis. The results of the characterization, has revealed that the oligomers with hydroxyl end group (PSOH) completion generate a single phase in the system carminic acid-oligostyrenes; also proved for a minor concentrations to 0.2%Wt of AC, there are a considerable integration between the pigment and the organic and inorganic matrix, with transparency and homogeneous coloration.

La polimerización en cadena vía radicales libres presenta gran versatilidad, ya que puede ser aplicado a una gran variedad de monómeros. Así, la producción de polímeros orgánicos, a lo largo de su historia ha utilizado agentes de transferencia de cadena para regular el crecimiento durante esta polimerización. En otro sentido, la producción de polímeros inorgánicos, a través del proceso sol-gel se ha llevado a cabo activamente en los últimos diez años, mostrando un incremento exponencial e imponiéndose como una técnica de elección con relación a otros enfoques, debido principalmente a las bajas temperaturas de operación, y al grado de pureza del compuesto obtenido. Por otro lado, el uso de pigmentos esta siendo cada vez más restringido, debido a su alto precio y labilidad. La presente investigación plantea la posibilidad de confinar pigmentos y así evitar su pronta degradación; el ácido carmínico (AC) por su parte, es uno de los pigmentos naturales de mayor uso e importancia comercial. De esta manera, se emplearon moléculas del AC para realizar un análisis sobre su interacción en matrices orgánicas a base de oligoestirenos con funcionalidad terminal variable; así como su integración en una matriz de dióxido de silicio. En estos sistemas se identificó una inusual agregación-interacción de las moléculas del AC a las matrices orgánicas e inorgánicas. Estas condiciones de interacción se observaron mediante un análisis morfológico, espectroscópico y térmico. Los resultados de la caracterización, revelaron que los oligómeros que poseen terminación hidroxilo (PSOH) generan una sola fase en el sistema ácido carmínico-oligoestirenos; así también, se advierte que a concentraciones menores al 0.2%Wt de AC, existe integración considerable del pigmento en las matrices analizadas, con transparencia y coloración homogénea.
Facultad de Ingeniería Química. Maestría en Ciencias en Ingeniería Química
Keywords: info:eu-repo/classification/cti/7; FIQ-M-2009-0030; Integración; Ácido carmínico; Oligoestirenos; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4807